2019
DOI: 10.1111/ter.12406
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Grenville–Sveconorwegian link in Rodinia reconstructions

Abstract: The Grenville, Sveconorwegian, and Sunsas orogens are typically inferred to reflect collision between Laurentia, Baltica, and Amazonia at ca. 1.0 Ga, forming a central portion of the Rodinia supercontinent. This triple-junction configuration is often nearly identical in otherwise diverse Rodinia reconstructions. However, available geological data suggest that although the Grenville and Sveconorwegian provinces shared a similar tectonic evolution from pre-1.8 to ca. 1.5 Ga, they record distinctly different tect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…Thus, Neoproterozoic tectonometamorphic activity in parts of the KNC, that reached temperatures and pressures of at least 750-800°C and 10-11 kbar at c. 710 Ma (Kirkland et al 2016), is not readily explained as having taken place on Baltica. Slagstad et al (2019) suggested that tectonic activity may have continued outboard of Baltica following retreat of the Sveconorwegian active margin; however, at present, there is little direct evidence to support this idea. In contrast, numerous papers argue that parts of the Laurentian margin were active until Laurentia-Gondwana break-up at around 600 Ma (Kirkland et al 2007;Cawood et al 2010;Strachan et al 2013).…”
Section: Exotic Components In the Scandinavian Caledonides And Their mentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, Neoproterozoic tectonometamorphic activity in parts of the KNC, that reached temperatures and pressures of at least 750-800°C and 10-11 kbar at c. 710 Ma (Kirkland et al 2016), is not readily explained as having taken place on Baltica. Slagstad et al (2019) suggested that tectonic activity may have continued outboard of Baltica following retreat of the Sveconorwegian active margin; however, at present, there is little direct evidence to support this idea. In contrast, numerous papers argue that parts of the Laurentian margin were active until Laurentia-Gondwana break-up at around 600 Ma (Kirkland et al 2007;Cawood et al 2010;Strachan et al 2013).…”
Section: Exotic Components In the Scandinavian Caledonides And Their mentioning
confidence: 97%
“…Iapetus break-up starting at c. 750-600 Ma is commonly understood with reference to the c. 1000 Ma Rodinia supercontinent (Li et al 2008); however, although the proximity of Laurentia and Gondwana in Rodinia is relatively well established, the position and orientation of Baltica is not (Hartz and Torsvik 2002;Slagstad et al 2019). Neoproterozoic tectonomagmatic events in Baltica are sparse.…”
Section: Exotic Components In the Scandinavian Caledonides And Their mentioning
confidence: 99%
“…The actual Sveconorwegian Orogen is characterised by terrane accretion events between 1.14 and 0.97 Ga arising from collision between Baltica and other continental fragments, followed by orogenic collapse at 0.9 Ga (Bingen et al 2008a). Although the Sveconorwegian orogeny was largely coeval, and likely also spatially related to the Grenville Orogen, the precise connection between these orogens is unclear, as well as the regional configuration, especially of Baltica at this time (Bingen et al 2008b;Slagstad et al 2013Slagstad et al , 2019Cawood and Pisarevsky 2017).…”
Section: The Grenville-sveconorwegian Orogenymentioning
confidence: 99%
“…Two main models exist for the tectonic evolution of the Sveconorwegian orogen: i) Bingen et al, (2008) and Möller et al (2015) suggest that the orogen formed by collision of Fennoscandia and Amazonia, ii), whereas Slagstad et al (2013Slagstad et al ( , 2017bSlagstad et al ( , 2018Slagstad et al ( , 2019 and Granseth et al (2020) suggest that the orogen formed as a result of accretionary processes along the Fennoscandian continental margin. In recent years most studies supports the model proposed by Slagstad et al (2013Slagstad et al ( , 2017bSlagstad et al ( , 2018Slagstad et al ( , 2019 and Granseth et al (2020).…”
Section: Sveconorwegian Orogenmentioning
confidence: 99%